2013
DOI: 10.3390/d5040779
|View full text |Cite
|
Sign up to set email alerts
|

Land and Forest Degradation inside Protected Areas in Latin America

Abstract: Using six years of remote sensing data, we estimated land and forest degradation inside 1788 protected areas across 19 countries in Latin America. From 2004, the rate of land and forest degradation increased by 250% inside the protected areas, and the land and forest degradation totaled 1,097,618 hectares. Of the protected areas in our dataset, 45% had land and forest degradation. There were relatively large variations by major habitat type, with flooded grasslands/savannas and moist broadleaf forest protected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 42 publications
1
51
1
2
Order By: Relevance
“…On a national level, Guatemala retains one of the highest deforestation rates in the Western Hemisphere (Hansen et al 2013), and the highest rate of protected area degradation in the Americas (Leisher et al 2013). By comparison, deforestation rates in certified forest concessions are relatively low (Hodgdon et al 2015).…”
Section: Impacts Of Selective Logging and Its Secondary Effects On Wimentioning
confidence: 97%
“…On a national level, Guatemala retains one of the highest deforestation rates in the Western Hemisphere (Hansen et al 2013), and the highest rate of protected area degradation in the Americas (Leisher et al 2013). By comparison, deforestation rates in certified forest concessions are relatively low (Hodgdon et al 2015).…”
Section: Impacts Of Selective Logging and Its Secondary Effects On Wimentioning
confidence: 97%
“…For example, Leisher et al [24] used the Terra-i dataset [25] developed by CIAT (International Center for Tropical Agriculture) to detect land and forest degradation inside protected areas in Latin America.…”
Section: State Of the Art: Implementing Operational Remote Sensing Inmentioning
confidence: 99%
“…A study across 49 protected areas in 22 countries found protected area category to be insignificant in predicting amount of land clearing [49]. Analysis of 1788 protected areas in Latin America found category V protected areas around the median of all categories in terms of vegetation loss [50]. Joppa et al [51] looking at natural vegetation cover in protected areas found little difference between different categories, except in West Africa where categories V and VI performed less well than stricter forms of protection.…”
Section: Do Protected Landscapes Work Effectively In Protecting Wild mentioning
confidence: 99%